avg rate of change = ( f(3) - f(2) )/(3-2)
= (0 - (-2)/1 = 2
..
the last one:
avg from x = 2 to x = 2.1
avg rate of change = ( f(2.1) - f(2) )/(2.1 - 2)
= (-1.89 - (-2)/(2.1-2)
= 1.1
y = f(x) = x^2 - 3 x
(a) Find the average rate of change of y with respect to x in the following intervals.
from x = 2 to x = 3
Incorrect: Your answer is incorrect.
from x = 2 to x = 2.5
Incorrect: Your answer is incorrect.
from x = 2 to x = 2.1
Incorrect: Your answer is incorrect.
(b) Find the (instantaneous) rate of change of y at x = 2.
1 answer